2020
DOI: 10.11604/pamj.2020.37.297.22928
|View full text |Cite
|
Sign up to set email alerts
|

HIV-free survival among breastfed infants born to HIV-positive women in northern Uganda: a facility-based retrospective study

Abstract: Introduction the HIV-free survival rate is the gold-standard measure of the effectiveness of interventions towards prevention of mother-to-child transmission of HIV in any setting. However, data on HIV-free survival among the HIV-exposed infants followed up in most low-resource settings are lacking. We determined the HIV-free survival among breastfed infants in two tertiary facilities in a resource-poor setting in northern Uganda. Methods we conducted a retrospective co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…Regarding to the feeding modality this study affirmed that 85.6% (95%CI: 81.6%-89.1%) of exposed infants were on EBF for the first six months. The result was much higher than the study findings reported from Nigeria (18.5%) [ 19 ]; Kenya (80.4%) [ 27 ], and Uganda (29.0%) [ 28 ]. It is also higher than reports from different parts of Ethiopia; 30.6% in Addis Ababa [ 29 ]; 77.3% in Debre Markos [ 30 ], 63.4% in the national and 50.9% sub national pooled prevalence [ 31 ].…”
Section: Discussioncontrasting
confidence: 70%
“…Regarding to the feeding modality this study affirmed that 85.6% (95%CI: 81.6%-89.1%) of exposed infants were on EBF for the first six months. The result was much higher than the study findings reported from Nigeria (18.5%) [ 19 ]; Kenya (80.4%) [ 27 ], and Uganda (29.0%) [ 28 ]. It is also higher than reports from different parts of Ethiopia; 30.6% in Addis Ababa [ 29 ]; 77.3% in Debre Markos [ 30 ], 63.4% in the national and 50.9% sub national pooled prevalence [ 31 ].…”
Section: Discussioncontrasting
confidence: 70%